Big Data of Source of Statistical Information: On the Example of the Book Publishing Industry - O. O. Horobets (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2019)
The article’s objective is to review domestic and foreign sources related with big data, in order to determine the potentials for their practical applications at industry level, with emphasis on book publishing. The main components of big data are highlighted, which form the reference model for big data management. An all-purpose model for big data processing is constructed by use of the analyzed information sources. A brief review of Hadoop big data analysis program is carried out. Applications of big data to improve business processes are analyzed with reference to renowned international companies, Internet platforms engaged in electronic commerce, and social networks. A brief review of Ukrainian cases of successful electronic commerce is made. As regards big data applications in book publishing, reference is made to the practices of Jellybooks company. The algorithm of big data collection by use of electronic book is constructed and illustrated. It is concluded that any industry is capable to adapt the successful practices of electronic commerce leaders after leaning them. As far as book publishing is concerned, a well-organized system for on-line data collection will open up opportunities for quick production of statistical information, extension of the range of statistical data, monitoring of the current book publishing performance and prediction of its future developments.